Biographical Notice Of Eckley B. Coxe, Jr. - Henry Drinker (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1916)
The Institute has lost a valued member by the death of Eckley B. Coxe, Jr. He bore the name of one who was largely instrumental in founding the Institute, and to whose support and guidance as active member, Vice-President, and President, the Institute owes. much. Eckley B. Coxe, Jr., was the nephew of the late Eckley B. Coxe. He held a large interest in the coal estates owned and developed by his family, and he was thus naturally led to take a continuing interest in mining matters, and for years and up to the time of his death was a full member of the Institute. He died at his residence, Drifton, Pa., on Sept. 20 last, aged 44. He was a member of the class of '93 of the University of Pennsylvania,. of which great institution he was a devoted alumnus. His educational and charitable activities were numerous, but his chief life-work and interest was in archeological investigation and research in Egypt, carried on through the Museum of the University of Pennsylvania of which Museum he was President. The discoveries made by the various expeditions financed and directed by him, and the notable publications issued by his direction and at his expense, chronicling the results, are among the most important researches ever made of buried Egypt. Mr. Coxe was a member of the International Historical Society and of many educational and charitable organizations. By his will, among other bequests, he left $500,000 to the Museum of the University of Pennsylvania and $100,000 to the University, the income of the latter fund to be applied to increasing the salaries of the professors of the Institution. He also left $100,000 to the Children's Hospital of Philadelphia, of which he was a manager, and in addition thereto $10,000 of which the income is to be applied in providing Christmas presents for .the child patients, and in providing an annual dinner for the patients and attendants of the hospital. He bequeathed $50,000 to Leonard Hall, an associate mission of the Episcopal Church, at South Bethlehem, Pa., $25,000 to the Epileptic Hospital and Colony Farm (Philadelphia) ; $50,000 to the Philadelphia Orthopaedic Hospital and Infirmary for Nervous Diseases; $15,000 to the United Charities of Hazleton, Pa., the income to be applied to the salaries of nurses; and $25,000 to the Mining and Mechanical Institute of the Anthracite Coal Region of Pennsylvania, founded by his uncle, Eckley B. Coxe, and of which Eckley B. Coxe, Jr., was an active trustee up to the time of his death. This Institute is known as one of the best preparatory schools for technical education in Pennsylvania, and is mainly devoted to extending an opportunity for education by day and night schools to the boys and young men of the Anthracite Region. Its principal is an alumnus of Lehigh University; it has an able local Board of Trustees, and an Advisory Board consisting of the Provost of the University of Pennsylvania, the President of Lafayette College, and the President of Lehigh University, all three of which institutions have established prize scholarships in the institute. Mr. Coxe carne of a distinguished ancestry, the record of which is fully given in the biographical notice of his uncle, Eckley B. Coxe, by Dr. R. W. Raymond, in Vol. XXV of the Transactions.`